PENGARUH KELOMPOK PENDUKUNG AIR SUSU IBU (KP-ASI) TERHADAP PERILAKU PEMBERIAN ASI EKSKLUSIF DAN STATUS GIZI BAYI 6-12 BULAN[The Influence of Breastfeeding Support Group (KP-ASI) to Exclusive Breastfeeding Practice and Nutrition Status of Infants Aged 6-12 Months] - Nur Hikmah Wati; Lailatul Muniroh (Media Gizi Indonesia, 2018)
Breast Milk is the best and nutritious food in early life for every infants born. Undernourishment in infants can cause growth and development disorders. The attainment of exclusive breastfeeding that still low in Wonoayu sub-district in 2015 becomes the base  the formation of breastfeeding support group (KP-ASI). The aim of this study was to observe the difference of exclusive breastfeeding record and nutrition status of infants aged 6-12 months of KP-ASI participant and non KP-ASI participant. This research was an analytic observational with cross sectional design. This research was done in the working area at Wonoayu and Buduran Health Center, district Sidoarjo. The sample were taken using stratified random sampling, the sample size 36 mothers of infants 6-12 months from KP-ASI participants and 36 mothers of infants 6-12 months from the non KP-ASI participants. The data collection was interviewed by using questionnaire and anthropometry measurements by using length board and baby scale. Data analysis of the research was Chi-Square test and Logistic Regression. The result showed that there was significant difference exclusive breastfeeding record between  groups (p=0.002)  but there was no difference in nutrition status of infants aged 6-12 months (p=0.547) in between both group. Mother employment status (p=0.022 OR=0.211), other family support (p=0.015 OR=O.195) becomes a confounding variable aside from implementation of KP-ASI (p=0.032 OR=3.701) which influence exclusive breastfeeding record. The conclusion of this study was that KP-ASI participant have 3,701 times higher chance to give exclusive breastfeeding the their babies compared with non-KP ASI nember there was no difference nutrition status of infants aged 6-12 months from both group it’ is suggested for Public Health Service of Regency Sidoarjo to develop and reactivate implementation of breastfeeding support group in other district to improve the practice of exclusive breastfeeding.